FRQ-CK1 interaction determines the period of circadian rhythms in Neurospora - Xiao Liu; Ahai Chen; Angélica Caicedo-Casso; Guofei Cui; Mingjian Du; Qun He; Sookkyung Lim; Hang J. Kim; Christian I. Hong; Yi Liu (Nature Communications, 2019)
Circadian clocks control daily rhythms of molecular and physiological activities. Here, the authors show that the interaction between proteins FRQ and CK1, rather than FRQ stability, is a major rate-limiting step in circadian period determination in the model fungus Neurospora.